2019
DOI: 10.1161/jaha.119.012738
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Determined Uric Acid and the Risk of Cardiovascular and Neurovascular Diseases: A Mendelian Randomization Study of Outcomes Investigated in Randomized Trials

Abstract: BackgroundHigher serum uric acid levels are associated with cardiovascular and neurovascular disease, but whether these relationships are causal is not known. We applied Mendelian randomization approaches to assess the association between genetically determined uric acid levels and outcomes under study in large clinical trials.Methods and ResultsWe used 28 genetic variants related to serum uric acid as instruments to perform a range of 2‐sample Mendelian randomization methods. Our analysis had statistical powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 50 publications
3
35
2
1
Order By: Relevance
“…16,17 Genetic causes of hyperuricemia have been linked with derangement of nitric oxide synthesis, and thus, endothelial dysfunction acts as a harbinger for inflammation and cardiovascular compromise. 18 The results of this study reveal that serum uric acid levels significantly rises with the severity of the disease, from a single vessel to triple vessel involvement. High sensitivity troponins levels were elevated in all the patients and based on that the diagnosis of MI was made.…”
Section: Discussionmentioning
confidence: 64%
“…16,17 Genetic causes of hyperuricemia have been linked with derangement of nitric oxide synthesis, and thus, endothelial dysfunction acts as a harbinger for inflammation and cardiovascular compromise. 18 The results of this study reveal that serum uric acid levels significantly rises with the severity of the disease, from a single vessel to triple vessel involvement. High sensitivity troponins levels were elevated in all the patients and based on that the diagnosis of MI was made.…”
Section: Discussionmentioning
confidence: 64%
“…The Mendelian randomization can be thought of as a naturally randomized controlled trial, based on the random allocation of alleles when passed from parents to offspring during the meiotic process, known as Mendel’s second law 31 . Recently, Efstathiadou et al 9 conducted a Mendelian randomization study to determine the clinically relevant causal effect between serum urate and the cardiovascular outcome. However, they failed to show any clinical causal relationship between uric acid and coronary heart disease, myocardial infarctions, the systolic blood pressure, or any type of ischaemic stroke 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Efstathiadou et al 9 conducted a Mendelian randomization study to determine the clinically relevant causal effect between serum urate and the cardiovascular outcome. However, they failed to show any clinical causal relationship between uric acid and coronary heart disease, myocardial infarctions, the systolic blood pressure, or any type of ischaemic stroke 9 . On the strength of that study, we selected nine genes from the 30 uric acid genes found in European populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, HU and gout may also be potential risk factors for hypertension, CVD, CKD, and the metabolic syndrome [ 8 , 10 ]. In studies using Mendelian randomization (MR) analyses, there is some support for obesity as a causal risk factor for HU and gout [ 11 ], whereas such studies have so far failed to support causality between HU and/or gout and other risk factors including CVD, CKD, and diabetes [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%